Transformation of National Law Towards a Just Democratic State - Sudaryat; Hamdiyah; Orias, Marco (Penerbit Mandalika Indonesia, 2025)
The transformation of national law is a strategic process in realizing a just and democratic state. This article aims to analyze the dynamics of legal reform in aligning national legal systems with the principles of democracy and social justice. Using a qualitative approach and library research method, this study examines various regulations, legal doctrines, and previous research related to the development of national law. The findings indicate that legal transformation involves not only normative changes in legislation but also institutional reform, public participation in the legislative process, and the strengthening of the rule of law. However, structural challenges such as legal dualism, regulatory overlap, and weak law enforcement remain significant obstacles to achieving substantive justice. Therefore, legal reform must be grounded in constitutional values, human rights, and public aspirations as the foundational elements in building a democratic and just rule of law state.